The study of adhesion between steel substrate, primer, and char of intumescent fire retardant coating - Puspitasari, W.C. (2019)
The aim of this study was to characterize the adhesion bonding of intumescent coating and the primer on steel substrate with respect to its mechanical, physical and chemical properties, before and after a fire test. The coated steel substrates were subjected to fire in a furnace at 950 °C for various durations ranging from 30, 45, and 90 to 120 min. The coatings were characterized by Thermogravimetric Analysis (TGA) while the char from fire test was characterized by Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR). For mechanical properties, the shear strength of the intumescent coating was measured for various coating thicknesses ranging from 1, 2, 3, 4, 10 to 22 mm through lap shear test. The changes in the adhesion bonding of the coatings, primer, and char with steel substrate microstructure were monitored using SEM. The microstructure observation indicated a profound mechanical interlocking mechanism between the primer coating and the steel substrate. Despite the two-hour fire test, the temperature of the steel substrate remained below 100 °C and no re-crystallization was observed. A considerable decrease in shear strength of the intumescent coating, primer and steel substrate from 1.95 MPa to 0.23 MPa was also measured as the thickness of the coating substrate was increased from 1 mm to 22 mm, respectively. © 2018 Elsevier B.V.